MESIN PENCACAH SAMPAH ORGANIK SKALA RUMAH TANGGA - Wirawan, I.K.G.; Sugita, I.K.G.; Suarda, M.; Astawa, K. (Buletin Udayana Mengabdi, 2023)
Kuta Utara is a district in Badung Regency, Bali, Indonesia, which consists of six villages, one of which is Kerobokan Kaja. The use of yards as land for ornamental plants in Kerobokan Kaja is very high, reaching up to 65%. The consequence of this large number of ornamental plants is the amount of leaf waste produced by plants in each house. This leaf litter can be used as a basic material for compost. These leaves need to be chopped in order to expand the contact area so that the decomposition process will be faster. Therefore it is necessary to make a household scale organic waste chopper machine. Aside from speeding up the decomposition process, this chopper machine also reduces the volume of organic waste, especially leaves by up to 60%. With this organic waste chopper, it is expected to reduce the volume of waste that burdens the Final Processing Site. Keywords: decomposition, chopping machines, volume reduction, organic waste, household scale